Optimizing inclusive human resource management at the laboratory elementary school - Besse Marhawati; Arifin Arifin; Sulkifly Sulkifly (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study examines the optimization of human resource management (HRM) in an inclusive elementary school at the Laboratory Elementary School of Gorontalo State University, focusing on planning, professional development, performance evaluation, and compensation. Using a qualitative case study, data were collected from principals, regular and special education teachers, administrative staff, and parents through interviews, observations, and document analysis. Findings indicate that HR planning is flexible and data-driven but remains reactive due to limited forecasting and formally trained staff. Professional development strengthens teacher competence through collaborative workshops, yet sustainability depends on integrating programs into school policy. Performance evaluation emphasizes formative feedback but lacks standardized criteria for inclusion-specific competencies, and compensation relies heavily on intrinsic motivation with minimal non-financial recognition. The study highlights that effective inclusive HRM requires systemic alignment across pedagogical, emotional, and institutional domains, balancing professional competence with teacher well-being, and offers practical insights for policy and school-level strategies to sustain inclusive education in the Indonesian context.